Numerical analysis of changes in the flow nature in a sonic flow with corrugated ribs - Khan, Ambareen; Aabid, Abdul; Abd Razak, Najihah; Khan, Sher Afghan; Baig, Muneer (Elsevier Ltd, 2025)
The study of turbulent flow at high inertia levels remains an area of investigation with the advent of the space shuttle and the design and development of supersonic/hypersonic missiles and aircraft. When the flow gets separated, there is an abrupt rise in the relief to the flow, resulting in a low-pressure recirculation region at the blunt base of the shells, rockets, and missiles. This study aims to assess the effectiveness of passive control as a corrugated rib at Mach unity for a pipe of diameter 25 mm for a length-to-diameter ratio (L/D ratio) = 1 to 6. The study was conducted for a nozzle pressure ratio of 1.5 to 5. At sonic Mach number, when the passive control is placed at various locations in the duct, the optimum location and height of the rib seem to be L/D = 0.5,1, 2, and 5 mm, resulting in a base pressure almost three to four times the ambient pressure where the flow from the nozzle sees corrugated part of the rib which sheds secondary vortices due the presence of the sharp corners. The control is adequate for the three mm height of the rib, but the maximum gain is at L/D = 2, and for other locations of the rib, the change in the pressure at the recirculation region is insignificant. The base pressure values remain the same when the rib is further moved downstream at L/D = 3 and 4, and the rib position variation is ineffective. Hence, based on the mission’s needs, one can select the size and position of the rib. Therefore, any increase in base pressure will enhance the range of missiles, rockets, aircraft bombs, and artillery shells, leading to enormous savings in fossil fuels, a reduction in carbon emissions, and a reduction in global warming.